2014
DOI: 10.1007/s10815-014-0351-8
|View full text |Cite
|
Sign up to set email alerts
|

Does IVF cleavage stage embryo quality affect pregnancy complications and neonatal outcomes in singleton gestations after double embryo transfers?

Abstract: Our study suggests that transfer of poor-quality embryos did not increase the risk of adverse outcomes; however, the quality of cleavage stage embryos significantly affected the miscarriage rate and ongoing pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 33 publications
4
45
1
1
Order By: Relevance
“…Embryo quality is one of the main predictors of success in IVF cycles [1, 2]. Many studies have shown a strong association between embryo morphology, implantation, and clinical pregnancy rates.…”
Section: Introductionmentioning
confidence: 99%
“…Embryo quality is one of the main predictors of success in IVF cycles [1, 2]. Many studies have shown a strong association between embryo morphology, implantation, and clinical pregnancy rates.…”
Section: Introductionmentioning
confidence: 99%
“…One report reviewed 340 singleton births after single‐cleavage embryo transfers and observed no significant difference in the parameters of the mean birthweight and infant height, umbilical blood analysis, placental weight, or umbilical cord length between the poor‐ and the good‐quality embryo transfers . One of the reports reviewed 11 721 cleavage‐stage double embryo transfers and demonstrated that the live births after the poor‐quality embryo transfers achieved the same pregnancy outcomes as those after the good‐quality embryo transfers did in terms of mean gestational week, delivery mode, SGA, LGA, PTD rate, and LBW . In agreement with these reports, this review's results demonstrate that the poor‐quality embryos did not increase the prevalence of adverse obstetric and neonatal complications.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated a strong association between morphologically poor‐quality embryos, a low clinical pregnancy rate, and low live birth rate per transfer . However, relatively few studies have reported associations between the embryo quality and miscarriage and live birth rates of clinical pregnancies due to the lack of evidence in evaluating these issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations